2020
DOI: 10.3389/fpls.2020.00949
|View full text |Cite
|
Sign up to set email alerts
|

New Rootsnap Sensor Reveals the Ameliorating Effect of Biochar on In Situ Root Growth Dynamics of Maize in Sandy Soil

Abstract: We investigated if subsoil constraints to root development imposed by coarse sand were affected by drought and biochar application over two seasons. Biochar was applied to the subsoil of pots at 20-50 cm depth in concentrations of 0%, 1%, 2%, and 3% (B0, B1, B2, and B3). Maize was grown in the same pots 1 week and 12 months after biochar application. The maize plants were fully irrigated until flowering; thereafter, half of them were subjected to drought. A new method for observing root growth dynamics and roo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 50 publications
2
7
0
Order By: Relevance
“…As root growth and rhizosphere processes alter soil properties, root development and distribution (in addition to the added biochar and ash) could also have had an impact the observed effects on water retention and evaporation. A positive effect of biochar on in situ root growth in coarse sandy subsoil (same type as used in the present experiment) has also been shown by Ahmed et al (2020), where small cameras (‘root‐snaps’) installed at 50 cm depth showed arrival of maize roots up to 9 days earlier in biochar‐amended subsoil compared to the un‐amended control. The authors ascribed this to reduced mechanical resistance and increased water content in the biochar‐amended subsoil.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…As root growth and rhizosphere processes alter soil properties, root development and distribution (in addition to the added biochar and ash) could also have had an impact the observed effects on water retention and evaporation. A positive effect of biochar on in situ root growth in coarse sandy subsoil (same type as used in the present experiment) has also been shown by Ahmed et al (2020), where small cameras (‘root‐snaps’) installed at 50 cm depth showed arrival of maize roots up to 9 days earlier in biochar‐amended subsoil compared to the un‐amended control. The authors ascribed this to reduced mechanical resistance and increased water content in the biochar‐amended subsoil.…”
Section: Discussionsupporting
confidence: 87%
“…Soil application of biochar (charred biomass) to low‐fertility sandy soils is increasingly been advocated as a means to improve soil fertility and concurrently mitigate climate change by carbon sequestration (Atkinson et al, 2010; Kuppusamy et al, 2016). Coarse sandy soils constitute a large proportion of the cropping and grazing land in the north‐western part of Europe (Ahmed et al, 2020). These soil types are characterized by having a low water holding capacity and by restricted growth of roots due to mechanical impedance of the subsoil.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…At this time, rehydration can compensate for the drought effect in the early stage. Through the analysis of root length of different diameter classes, this study (Figure 6) found that the proportion of fine roots of summer maize increases under Frontiers in Earth Science frontiersin.org drought stress, which is consistent with the research of some research scholars (Florian et al, 2019;Ahmed et al, 2020), under appropriate drought stress, the proportion of fine root length and root surface area will increase to strengthen water use efficiency, ensure the formation of a large underground system to support the normal operation of the whole plant, enhance adaptability to adverse environment (Smucker and Aiken, 1992;Lorenc et al, 2018).…”
Section: Adaptive Ways Of Root Morphology Under Drought Stresssupporting
confidence: 88%
“…Two quadrants were taken from each sampling site more than 100 m apart, located and recorded using GPS with latitude and longitude, and numbered sequentially according to the order of sampling sites (Wu et al, 2021a). The weeds on the surface were removed, and the soil was extracted using stainless cutting rings (100 cm 3 ) and used to determine the water content of the soil using the oven-drying method at 105 °C and the bulk density of the surface soil (0-10 cm) (Wang et al, 2015;Ahmed et al, 2020). Soil samples were also collected from the surface at a depth of 0-10 cm using a soil auger.…”
Section: Soil Sample Data Acquisition and Processingmentioning
confidence: 99%